A new house - Manley, Deborah; Simpson, Julie (Milwaukee : Raintree Children Books, 1979)
Simple text and illustrations describe the building of a house and the experience of moving into a new neighborhood. The reader is encouraged to look at, think about, and describe similar experiences.
2.7
K-3
Keywords: House construction -- Juvenile literature; House construction; Moving, Household; House construction; Moving